Guidelines for Drought Management in Thailand - Jiteurangkoon, Patcharee; Norkaew, Yutthasart (Journal of Public Administration Chiang Rai Rajabhat University, 2021)
The aim of this article is to study the approaches for drought management in Thailand. This study was conducted by collecting data from various sources such as documentary researches, academic documents, academic articles, analytic studies and news available in various media. The collected data were analyzed to determine what approaches are appropriate for drought management in Thailand. The results revealed that there are three approaches of systematic and sustainable drought management that lead to results-based management regarding on long-term drought preventions, as follows: The first approach is that key agencies should be set up with respect to their responsible roles of drought management., The second approach is that the government sector needs to integrate the collaborative efforts between all the government agencies involved and public sectors. And the third approach is that public hearings should be held to draw up guidelines for sustainable water management of drought-stricken areas.